The Impact of Islamic Finance Development, Economic Growth, Function of Regional Government Budgets on Carbon Emissions in Indonesia - Mamduh, Muhammad Faizul; Rusgianto, Sulistya (Universitas Muhammadiyah Semarang, 2024)
Carbon emissions are a pressing global issue, with international agreements such as the Kyoto Protocol, Paris Agreement, and COP26 aiming to limit temperature rise and achieve net zero emissions. This research investigates the impact of Islamic financial development, economic growth, and government budget functions on carbon emissions in Indonesia, using panel data from 2018 to 2022. The study reveals that Islamic finance, specifically Sharia banking financing, significantly reduces carbon emissions. Conversely, economic growth (GRDP) is positively associated with carbon emissions, while the government’s environmental budget shows a negative relationship but lacks statistical significance. These findings highlight the effectiveness of Islamic finance in promoting environmentally sustainable practices and underscore the need for more effective government budgeting and regulatory measures. Future research should explore a broader range of Islamic finance sectors and budgetary functions to provide a more comprehensive understanding of their impact on carbon emissions. This study’s insights can guide policymakers in reinforcing successful strategies and developing new approaches to achieve emission reduction goals.